The world's water crisis - Garner, Simon; Hillel, John.; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2003)
This program looks at the world's dwindling fresh water supply and it stresses the need to conserve water. It features case studies, including a plan to pipe irrigation water and a water-saving housing development in Melbourne and offers hints on how to conserve water around the home.
Keywords: Water conservation; Water-supply.